A comprehensive genetic profile of phyllodes tumours of the breast detects important mutations, intra-tumoral genetic heterogeneity and new genetic changes on recurrence. - Jones, A; Mitter, R; Springall, R; Graham, T; Winter, E; Gillett, C; Hanby, A; Tomlinson, I; Sawyer, E (2008)
The aims of this study were to identify genetic changes associated with malignant progression of the fibroepithelial neoplasms, phyllodes tumours of the breast (PTs), and to ascertain whether genetic progression occurs when PTs recur locally. A further aim was to assess whether the genetic data support the classification of these tumours into three subtypes, benign, borderline and malignant. 126 PTs (37 benign, 41 borderline, 48 malignant) were analysed by either array-CGH or the Illumina Goldengate assay. The large-scale genetic changes associated with malignant/borderline phenotypes were +1q, +5p, +7, +8, -6, -9p, -10p and -13. Cluster analysis of the array-CGH data supported the division of malignant and borderline PTs into two separate groups, one comprising almost all malignant lesions and the other, benign and borderline tumours. Interstitial deletions of 9p21 that involved the p16INK4a locus were present in many malignant/borderline PTs, and some of these appeared to cause homozygous loss. Loss of expression of p16INK4a was found frequently and this was associated with 9p deletion; we also identified one p16INK4a mutation and evidence of methylation of p16INK4a in malignant PTs. Our evidence shows that inactivation of this gene is important in the development of malignant PTs. In selected PTs, multiple areas of stroma were isolated and analysed separately by array-CGH. We found considerable intra-tumoral genetic heterogeneity. Analysis of paired primary and recurrent tumours showed that recurrent tumours often acquired new genetic changes; in particular, benign tumours tended to acquire changes characteristic of the malignant/borderline phenotype. We believe it likely that unfavourable sub-clones not easily identified by histology account for the unpredictable clinical behaviour of these tumours.